Environmental risk communication in China : actors, issues, and governance - Jai, Dai, 1976-; Fanxu, Zeng, 1978- (Abingdon, Oxon ; New York : Routledge, 2022)
"The role of media is becoming increasingly important as globalization has developed. Given fast social transformation and technological development in China, the consequent environmental and health risks demand citizens integrate the communication and prevention of such risks as a significant part of their daily life. This book systematically discusses the communication process of typical environmental risk issues, and the complex interaction among multiple actors, including the public, media, experts and government in contemporary China. From a media-centered perspective, it applies major theories in the field of risk communication, and uses a variety of empirical research methods to unravel the complicated and unique experience of risk communication and governance. Combining theoretical reflections with real-life examples of Chinese scenarios, the authors not only encourage a dialogue between Western and Chinese academia but also inspire students and practitioners to apply risk communication theories to solving real-life problems. The book will appeal to students, scholars and practitioners of risk and environmental communication studies"--
Translated from the original Chinese into English.
"English version by permission of Tsinghua University Press"--Title page verso.
Keywords: Climatic changes in mass media; Risk communication -- China; Climatic changes -- Press coverage -- China; Climatic changes -- Social aspects -- China; SCIENCE / Environmental Science; POLITICAL SCIENCE / Public Policy / Environmental Policy